UPAYA HUKUM SATGAS WASPADA INVESTASI DALAM PENANGGULANGAN INVESTASI FIKTIF - Muhammad Rizqi Ulil Abshor (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2023)
Not a few residents have become victims of criminal acts of collecting customer funds that were carried out illegally masked as investment, the reasons behind which are (1) economic side where a resident wants a lot of profit without thinking regarding what is to come, (2) environmental side in which a resident only pays attention to other customers who are around their environment, namely those who have higher education or occupational strata so that other residents believe in fictitious/illegal fundraising actions, and (3) the application of law to suspects who until now not optimal and not a deterrent for other suspects who think that if they commit these actions they will only be given a prison sentence of after serving a few years in prison, they can reap the benefits of their criminal activities. Actions of Investment Alert Task Force when managing company behavior in the unlawful fundraising sector were adjusted to the course of the investigation of Article 49 paragraph 3 where the success or failure of the law being enforced depends on the framework of law, legal essence, and legal norms.